Le silence et le cri : Salomé, d’Oscar Wilde à Richard Strauss - Pascal Aquien (Sillages Critiques)
Wilde’s play and Strauss’s opera can be considered as the acme of the literary, pictorial and musical currents that have been exploring the theme of Salome since the Middle Ages. The two works are however radically different. Unlike Wilde whose écriture is based on unlikely metaphors and a Maeterlinck-like art of the implicit, Strauss’s music and voices violently express what is more mildly suggested by the play, the primacy of the body over aesthetic constructions. On the one hand, Wilde’s poetical mode of composition is based on his fascination for the unspeakable, on the other hand Strauss’s dramatic expressionism tends to unveil the mystery of sexual desire. Yet, the article will show that the play and the opera broadly converge in the same direction, the issue at stake being in both cases silence beyond language.